DRAMATURGI PADA FILM YOU’VE GOT MAIL - Andre Ikhsano; Asifa Fauzia (Commed : Jurnal Komunikasi dan Media, 2022)
Every human being naturally wants peace, but on the other hand, contradictory traits are also present in the form of hostility and conflict. The film You've Got Mail tells the story of the two main characters who have conflicts with each other in the real world and at the same time also establish good relations with each other through e-mail. This duality is unique and interesting to study more deeply through Erving Goffman's dramaturgical perspective in the form of a front stage and a backstage which can dissect two sides in a social conflict between individuals. Research-based on the constructivism paradigm with a qualitative approach and through Barthes' semiotic analysis, which focuses on four scenes in the film you've got mail; managed to find that the front stage and backstage elements are described in detail, and it can be seen that the front stage is more dominant than the backstage. This has implications for impression management which is thicker on the element of imaging by the communicator. Keywords: Conflict, Dramaturgy, Front Stage, Back Stage, Impression Management